Research on the Construction Mechanism and Improvement Path of the Initiative of International Chinese Teachers’ Online Teaching from the Perspective of Social Cognitive Theory - WU, YI; Gaikwad, Sophia Sandeep (Journal of Ecohumanism, 2024)
Driven by globalization and digitalization, international Chinese teaching is undergoing profound changes, and online teaching has become an important development trend. Based on social cognitive theory and grounded theory, this study uses a sample of 463 international Chinese teachers from 32 countries around the world to explore the construction mechanism and improvement path of teachers’ online teaching initiative. The study found that: (1) International Chinese teachers’ online teaching initiative presents a progressive construction model of "cognition-emotion-behavior", in which digital teaching cognition, cross-cultural teaching emotion and innovative teaching behavior constitute the core elements; (2) Teacher initiative is affected by individual factors (digital literacy, cultural adaptability), environmental factors (organizational support, technical infrastructure) and interactive factors (quality of teacher-student interaction, peer learning network); (3) Based on the three-way interaction of social cognitive theory, a "perception-adaptation-innovation" teacher initiative improvement model is constructed. This study is the first to integrate social cognitive theory with teacher initiative research, revealing the internal mechanism of international Chinese teachers’ online teaching initiative, and providing theoretical guidance and practical paths for promoting the high-quality development of international Chinese education.